Cryptocurrencies vs Stocks: Analyzing Returns, Risks, and Performance to Determine the Best Investment - Reksha Laksana; R. Rita Avianty; Erik Nugraha; Hadi Ahmad Sukardi (Journal of Business and Economics Research (JBE), 2026)
This study compares the investment performance of selected cryptocurrencies and stocks over the period 2020–2024 by analyzing returns, risk and relative performance. A quantitative descriptive approach was employed with a saturated sample of 40 assets (cryptocurrencies and stocks) and 2,400 monthly closing-price observations. The analyzed metrics include monthly returns, volatility (as a proxy for risk) and the Sharpe ratio for risk‑adjusted performance. Results indicate that cryptocurrencies produced higher average returns but exhibited substantially greater volatility; DOGE shows the highest risk with a value of 14.02955. In a risk-adjusted comparison based on the Sharpe ratio, TRX achieves the highest Sharpe ratio with a value of 1.29783, followed by NVDA at 1.21917 and AVGO at 1.15028, suggesting that several assets delivered superior returns with relatively controlled risk. Yearly comparisons revealed shifting performance leaders, reflecting temporal market dynamics across the five‑year window. These findings imply that portfolio allocations should explicitly consider the trade‑off between higher returns from cryptocurrencies and their increased volatility, and should incorporate risk‑adjusted metrics such as the Sharpe ratio when selecting assets. This study can be used as a reference to improve investors' understanding of asset performance and the risks of cryptocurrencies and stocks, and can encourage further research on investment analysis and risk management across various asset classes.